Etika Jurnalistik dan Jurnalisme Bencana pada Pemberitaan Gunung Agung di Portal Berita Balipost.com - Redi Panuju (Jurnal ILMU KOMUNIKASI, 2018)
This study discusses the news of Gunung Agung disaster in Balipost.com from the aspect of journalism ethics and disaster journalism. Disaster journalism is required to report disaster objectively, though media cannot be separated from business goals. Ethnographic content analysis is conducted as research method. The result shows that Balipost.com has applied the principle of journalism code of ethics and the principles of disaster journalism. The news tend not to use indepth reporting, which is less thorough, lack of direct observation results, but it averts the violation of ethics.